Efektifitas Penggunaan Media Pembelajaran Quizizz Terhadap Minat Dan Hasil Belajar Matematika Siswa Kelas XI IPA MAN 2 Sinjai - Khusnul Mawaddah Amsul; Irmayanti Irmayanti; Fitriani Fitriani; Sudirman P (Universitas Islam Ahmad Dahlan (UIAD) Sinjai, 2022)
Abstract The Effectiveness of Using Quizizz Learning Media on Interest and Mathematics Learning Outcomes of Class XI IPA MAN 2 Sinjai. Essay. Sinjai: Tadris Mathematics Study Program, Faculty of Tarbiyah and Teacher Training Islamic Instutute of Muhammadiyah Sinjai, 2021. This study aims to determine the effectiveness of the use of Quizizz learning media on the interest and learning outcomes of mathematics students in class XI IPA MAN 2 Sinjai. The type of research used in this research is experimental research with pre-experimental research design in the form of one group pretest posttest design, with a quantitative approach. The population in this study were all students of class XI IPA MAN 2 Sinjai totaling 24 people using total sampling technique in sampling. The results of the study based on descriptive analysis showed that: (1) the average score of students' interest in learning mathematics after the quizizz learning media was applied was 87.58 and was in the high category; (2) there is an increase in students' interest in learning mathematics after the application of the quizizz learning media by obtaining an average normalized gain value of 0.3 which is at the medium category level; (3) the average score of students' mathematics learning outcomes after the quizizz learning media was applied was 80.53 and was in the high category; (4) there is an increase in students' mathematics learning outcomes after the quizizz learning media is applied by obtaining an average normalized gain value of 0.4 which is at the level of the medium category. Based on the results of inferential statistical analysis, obtained Sig. (2-tailed) < 0.05 or 0.000 < 0.05, so that H0 is rejected and Ha is accepted, which means that there is an increase in students' interest and learning outcomes in mathematics after the application of the Quizizz learning media. From the results of this study, it can be concluded that the use of Quizizz learning media is effective on the interest and learning outcomes of mathematics students in class XI IPA MAN 2 Sinjai. Keywords: Effectiveness, Quizizz, Interests and Learning Outcomes Abstrak Efektivitas Penggunaan Media Pembelajaran Quizizz terhadap Minat dan Hasil Belajar Matematika Siswa Kelas XI IPA MAN 2 Sinjai. Skripsi. Sinjai: Program Studi Tadris Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAI Muhammadiyah Sinjai, 2021. Penelitian ini bertujuan untuk mengetahui efektivitas penggunaan media pembelajaran quizizz terhadap minat dan hasil belajar matematika siswa kelas XI IPA MAN 2 Sinjai. Jenis penelitian yang digunakan pada penelitian ini adalah penelitian eksperimen dengan desain penelitian pre-eksperimental design berupa one group pretest posttest design, dengan pendekatan kuantitatif. Populasi pada penelitian ini adalah seluruh siswa kelas XI IPA MAN 2 Sinjai yang berjumlah 24 orang dengan menggunakan teknik total sampling dalam pengambilan sampel. Hasil penelitian berdasarkan analisis deskriptif menunjukkan bahwa : (1) skor rata-rata minat belajar matematika siswa setelah diterapkan media pembelajaran quizizz adalah 87,58 dan berada pada kategori tinggi; (2) terjadi peningkatan minat belajar matematika siswa setelah diterapkan media pembelajaran quizizz dengan memperoleh rata-rata nilai gain ternormalisasi adalah 0,3 yang berada pada tingkat kategori sedang; (3) skor rata-rata hasil belajar matematika siswa setelah diterapkan media pembelajaran quizizz adalah 80,53 dan berada pada kategori tinggi; (4) terjadi peningkatan hasil belajar matematika siswa setelah diterapkan media pembelajaran quizizz dengan memperoleh rata-rata nilai gain ternormalisasi adalah 0,4 yang berada pada tingkat kategori sedang. Berdasarkan hasil analisis statistik inferensial, diperoleh Sig.(2-tailed) < 0.05 atau 0.000 < 0.05, sehingga H0 ditolak dan Ha diterima yang berarti bahwa terjadi peningkatan minat dan hasil belajar matematika siswa setelah penerapan media pembelajaran quizizz. Dari hasil penelitian ini dapat disimpulkan bahwa penggunaan media pembelajaran quizizz efektif terhadap minat dan hasil belajar matematika siswa kelas XI IPA MAN 2 Sinjai. Kata kunci: Efektivitas, Quizizz, Minat dan Hasil Belajar